Intensive insulin therapy implementation by means of planned versus emergent change approach. Issue 3 (23rd October 2015) - Luiking, Marie‐Louise; van Linge, Roland; Bras, Leo; Grypdonck, Maria; Aarts, Leon
ABSTRACT: Background: Nurses' participation in decisions about new care procedures and protocols is potentially of benefit for patient outcomes. Whether nurses' participation in decisions is allowed in the implementation of innovations depends on the implementation approach used for the introduction. A planned change implementation approach does not allow it, an emergent change implementation approach does. Aim: To compare a planned change and an emergent change implementation approach to introduce an intensive insulin therapy to an intensive care unit (ICU). Design: A prospective comparative study in an ICU in the Netherlands of two teams of nurses using either implementation approach. Methods: Pre‐introduction of the comparability of the two teams was assessed. The nurse compliance to the protocol was assessed as being nurses' behaviour according to the protocol and leading to acceptable glucose values. The effectiveness of the implementation was assessed by measuring the percentage of patients' glucose values within the target range, the occurrence of hypoglycaemic events and the time to glucose value normalization. Data were collected from December 2007 till January 2009. Results: In the emergent change approach team there was better nurse compliance measurements than in the planned change approach team (83.5% vs 66, 8% conform protocol), a better percentage of glucose values in the target range (53, 5% vs 52.8%) and a shorter time to glucose value normalization. Conclusion: The implementation approach allowing nurse participation was associated with better nurse compliance and patient outcome measurements. The implementation approach did not conflict with introducing an evidence‐based innovation. It was also associated with more effective adaptation of the protocol to changing circumstances. Relevance for clinical practice: When a new treatment requires adaptability to changing circumstances to be most effective, nurses' participation in decisions about the implementation of the treatment should be considered.